PENGARUH OLAH RAGA JOGGING TERHADAP PENURUNAN STRES PADA REMAJA YANG MENGALAMI SINDROME PREMENSTRUASI DI MA AL BADRIYAH RARANG TERARA KABUPATEN LOMBOK TIMUR - Ilmi, Nurul; Halwiani, Baiq; Suryatno, Hadi; Putra, Ageng Abdi; Astuti, Febriati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Adolescent is a transitional period from childhood to adulthood and has the most conflicts in one's life. One of the changes taking place among the adolescents, especially female, is the change in sexuality. The development of the sexual organs is marked by premenstrual syndrome accompanied by uneasy feelings, especially stress.Jogging is an easy and cheap activity which can be done by anybody; yet it is very beneficial for body health, especially reducing the level of stress. However, the effectiveness of jogging to reduce the stress has not been keenly observed so far. This study is a pre-experimental study to find out the decrease of level of stress the adolescents experiencing premenstrual syndrome who are given jogging treatment. The number of samples in this study was 40 respondents, taken through accidental sampling. Data is collected by means of questionnaire and interview. The data, Stres level, is analyzed using wilcoxon match pairs test with error level of 5%. The result shows that there is a significant decrease of the stress level after the treatment, indicated by the fact that the value of z calculation of 5.41 is greater than the value of z table of 1,65. Therefore, it is suggested that adolescents practice jogging as a means of reducing of stress level when experiencing premenstrual syndrome.